Theory, Totality, Critique: The Limits of the Frankfurt School Critical Theory, Marxism and Modernity - Philip Goldstein (Studies in 20th & 21st Century Literature, 1992)
Theory, Totality, Critique: The Limits of the Frankfurt School Critical Theory, Marxism and Modernity by Douglas Kellner.
Keywords: Frankfurt School; WWII; Critical Theory Marxism and Modernity; Post-modernism; society; theory; socio-historical perspective; Marxism; Marxist rhetoric; communism; communistic parties; totalization; totalizing approach